Letter - Boston Joint Strike Committee, 6 May 1926 (Boston)
1926-05-06 "Letter - Boston Joint Strike Committee, 6 May 1926" [g0358001.jpg], 6 May 1926, Boston Joint Strike Committee Local Organisation